Opschrift gedenksteen:"Aan den stichter en leider van den Nederlandschen Bond van Personeel in Overheidsdienst"
Opschrift gedenksteen:"Aan den stichter en leider van den Nederlandschen Bond van Personeel in Overheidsdienst".